Respiratory syncytial virus prevention in children with congenital heart disease: who and how? - Nam Kyun Kim; Jae Young Choi (Korean Pediatric Society, 2011)
Respiratory syncytial virus (RSV) is a major cause of respiratory infection in children. Most of the pediatric population have RSV infection before the age of 2, and recurrent infections are common even within one season. Chronic lung disease, prematurity, along with congenital heart disease (CHD) are major risk factors in severe lower respiratory infection. In hemo-dynamically significant CHD patients with RSV infection, hospitalization is usually needed and the possibility of treatment in intensive care unit and the use of mechanical ventilator support are known to increase. Therefore the prevention of RSV infection in CHD patients is mandatory. The current standard for RSV prevention is immunoprophylaxis by palivizumab. Immunoprophylaxis is recommended monthly in hemodynamically significant CHD patients, up to 5 months. Motabizumab, a second generation drug and newly developing RSV vaccines are also expected to play a key role in RSV prevention in the future. The prophylaxis of RSV infection in CHD patients is cost-effective in both the medical aspect of the patients as well as the socio-economic aspect. Therefore an effort to promote prevention should be made by not only the family of the patients but also by the government.